The Internal Recycle Reactor Enhances Porous Calcium Silicate Hydrates to Recover Phosphorus from Aqueous Solutions - Wei Guan; Shichao Tian (Journal of Chemistry)
In this experiment, the porous calcium silicate hydrates (P-CSHs) were prepared via a hydrothermal method and then modified by polyethylene glycol (PEG). The modified P-CSHs combined with an internal recycle reactor could successfully recover the phosphorus from electroplating wastewater. The modified P-CSHs were characterized by X-ray diffraction (XRD), N2 adsorption-desorption isotherms, and Fourier transform infrared spectroscopy (FT-IR). After compared with different samples, the modified P-CSHs-PEG2000 sample had larger specific surface area of 87.48 m2/g and higher pore volume of 0.33 cm3/g, indicating a high capacity for phosphorus recovery. In the process of phosphorus recovery, the pH value of solution was increased to 9.5, which would enhance the recovery efficiency of phosphorus. The dissolution rate of Ca2+ from P-CSH-PEG2000 was fast, which was favorable for phosphorus precipitation and phosphorus recovery. The effects of initial concentration of phosphorus, P-CSHs-PEG2000 dosage, and stirring speed on phosphorus recovery were analyzed, so the optimal operation conditions for phosphorus recovery were obtained. The deposition was analyzed by XRD, N2 adsorption-desorption, and SEM techniques; it was indicated that the pore volume and surface area of the P-CSHs-PEG2000 were significantly reduced, and the deposition on the surface of P-CSHs-PEG2000 was hydroxyapatite.